Using Phenomenology to Understand Experiences of Racism for Second-Generation South Asian Women - Beharry, Pauline; Crozier, Sharon (Canadian Journal of Counselling and Psychotherapy, 2008)
The purpose of this investigation was to describe the lived experiences of racism for second-generation Canadian women of South Asian descent and how this affected their identity. Six adult co-researchers shared their experiences of what occurred when faced with racism. A phenomenological approach was employed, out of which five categories emerged. Findings indicated that the acculturative process in negotiating experiences of racism resulted in these women having a multifaceted, complex identity. These findings offer new understandings of how coping responses served to assist the women in this study. This study contributes to counsellor awareness and knowledge when working with ethnic groups.